Democracy and Islamist Violence: Lessons from Post‐Mubarak Egypt1. (May 2014) - Drevon, Jérôme
Abstract This article explores the contentious relation between the absence of democracy in the Middle East and the use of armed violence by Islamist groups in light of the Arab Spring. Its main objective is to decipher the evolving positions of former and current groups who used or promoted violence and to relate them to broader academic debates on violence and democracy on the one hand, and deradicalization on the other. This research demonstrates that the large majority of former Islamist militants in Egypt reject any sort of violence in post‐Mubarak Egypt, even if they have not all renounced their religious legitimization of violence in the past. Second, it reveals that even if they maintain a religious opposition to democracy in Egypt, the opening of political opportunities and their progressive joining of the political process has favorably led most of them to accept democratic practices in reality. Third, it adds that the voice of those currently promoting violence in Egypt has been marginalized and that their main alternative has been the promotion of armed violence in Syria; and last, it stresses two potential security threats unrelated to the opening of political opportunities in post‐Mubarak Egypt and to the general debate on democracy and violence. First, local grievances in Sinai have led to violence in the past and are still to be dealt with. Second, the current political deadlock can potentially lead to localized and specific armed activities that could start a cycle of violence. This research is based on field research in Egypt and uses repeated interviews of leaders and members of the two main former militant groups, al‐Jama῾ah al‐Islamiyya (the Islamic Group) and Jama῾ al‐Jihad (the Jihad Group) as well as interviews with militants of the salafi jihadi trend and their supporters in Cairo.